2020
DOI: 10.3389/fcimb.2020.557027
|View full text |Cite
|
Sign up to set email alerts
|

In the Search of Potential Serodiagnostic Proteins to Discriminate Between Acute and Chronic Q Fever in Humans. Some Promising Outcomes

Abstract: Coxiella burnetii is the agent that causes acute and chronic Q fever infections in humans. Although the isolates studied so far have shown that the two forms of the disease differ in virulence potential thus, implying a variance in their proteomic profile, the methods used do not deliver enough discriminatory capability and often, human infections may be mis-diagnosed. The current study adds further knowledge to the results that we have already published on the Coxiella outer membrane protein 1 (Com1). Herein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…GroEL and DnaK were also persistent and accurate molecular markers described by Xiong et al [32,37,44,[46][47][48]. Using multiplex serology, they achieved specificities of 84% and 79%, respectively, and sensitivities of 79% and 68%, respectively.…”
Section: Discussionmentioning
confidence: 89%
“…GroEL and DnaK were also persistent and accurate molecular markers described by Xiong et al [32,37,44,[46][47][48]. Using multiplex serology, they achieved specificities of 84% and 79%, respectively, and sensitivities of 79% and 68%, respectively.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, 77% of the C. burnetii-reactive group was also reactive to at least one of the identified epitopes (Table 4). These data reinforce the need to identify linear B-cell epitopes in other promising serological markers-such as OmpA [89], C. burnetii macrophage infectivity potentiator protein (Cb-Mip) [90], and YbgF [85]-in order to improve the development of novel tools for the diagnosis of C. burnetii.…”
Section: Discussionmentioning
confidence: 55%
“…Moreover, despite the possibility of mistaking Q fever for influenza, dengue, malaria, leptospirosis, and other infectious diseases [30], in Brazil, only suspected rickettsiosis cases are investigated as Q fever, corroborating the underreporting of this zoonosis, and explaining the limited number of C. burnetii-reactive samples in this study (n = 26). Remarkably, similar-sized samples were previously used to successfully define C. burnetii proteins as antigens to serological tests [37,[84][85][86], indicating that the number of patients used in our study was sufficient to prove the natural immunogenicity of the identified epitopes.…”
Section: Discussionmentioning
confidence: 67%
“…31 This Com1 antigen study found a Se of 77% and Sp of 72%, without significant differences among species (sheep, goat, and cattle), 31 although Com1 is reported to be more sensitive and specific than Ybgf in humans. 16,25,31 This discrepancy might be attributed to different immune responses against these antigens between humans and ruminants, as well as the choice of sera used for the assay. Certainly, our ELISA is not a useful tool for routine testing, but further experiments are needed to compare the results with a larger number of true-positive and true-negative sera.…”
Section: Discussionmentioning
confidence: 99%
“…38 In human medicine, recent attempts to use Ybgf in a recombinant ELISA revealed good Sp (close to 90%) but poor Se (12.5-21%). 16,25 We evaluated the efficiency of this recombinant antigen for the detection of antibodies against Coxiella burnetii in ruminants.…”
mentioning
confidence: 99%